Nutrient Cycling in Young Teak Plantation I - Restitution of Nutrients through Litter and Rain-wash - Rajagopal, K.; Buvaneswaran, C.; Subramanian, V.; George, M. (Indian Forester, 2005)
Studies on different pathways of nutrient return through litterfall and rain-wash were carried out in a young teak (Tectona grandis L. f.) plantation at five years age (Density 2500 trees/ha). The total litter produced was 4574 kg/ha and the nutrients returned amounted to : nitrogen - 46kg/ha; phosphorus- 3 kg/ha; potassium 39kg/ha; calcium 86kg/ha; and magnesium 21kg/ha. Studies on interception of rainfall have shown that, the total incident rainfall recorded for this study during the year 2000 was 1013 mm. Of which, 28.97% was intercepted by the canopy, while 7.66% was accounted for stemflow and 63.37% for through fall. With regards to nutrients return through rain-wash, it was found that, throughfall returned more quantities of all nutrients, than stemflow. Of the total return (litter + rain wash) of various nutrients, maximum amount (kg/ha) of return was accounted for calcium (87.40) followed by nitrogen (46.56), potassium (40.31), magnesium (22.13), and the least for phosphorus (3.31). Among these two pathways of nutrients return, litterfall contributed greater amount of all nutrients (from 95 to 99%), when compared to rain wash (0.8 to 4.9%). These results were compared and discussed with nutrients return and nutrient cycling in 20 years old teak plantation and suggest intensive silvicuItural practices in teak plantations during the initial stages of growth to enhance the productivity.